2023
DOI: 10.1021/acs.jmedchem.3c01116
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design and Synthesis of Stapled 10Panx1 Analogues for Use in Cardiovascular Inflammatory Diseases

Arthur Lamouroux,
Malaury Tournier,
Debora Iaculli
et al.

Abstract: Following a rational design, a series of macrocyclic ("stapled") peptidomimetics of 10 Panx1, the most established peptide inhibitor of Pannexin1 (Panx1) channels, were developed and synthesized. Two macrocyclic analogues SBL-PX1-42 and SBL-PX1-44 outperformed the linear native peptide. During in vitro adenosine triphosphate (ATP) release and Yo-Pro-1 uptake assays in a Panx1expressing tumor cell line, both compounds were revealed to be promising bidirectional inhibitors of Panx1 channel function, able to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Gene silencing approaches may also be challenging as airway connexins/pannexins may compensate for each other, as observed, for example, in keratinocytes [125,148]. The ongoing development of connexinand pannexin-targeting peptides may help to address this question [149][150][151]. As the well-differentiated airway epithelium accommodates with low connexin expression, any changes in their expression and/or regulation may alter the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing approaches may also be challenging as airway connexins/pannexins may compensate for each other, as observed, for example, in keratinocytes [125,148]. The ongoing development of connexinand pannexin-targeting peptides may help to address this question [149][150][151]. As the well-differentiated airway epithelium accommodates with low connexin expression, any changes in their expression and/or regulation may alter the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the problems of the low proteolytic stability of Panx1 inhibitors developed in previous studies, the helical stapling method was applied. As a result, it was reported that the two analogs generated achieved a twofold increase in the inhibitory effect as well as a 30-fold increase in the stability profile under physiological conditions (Lamouroux et al 2023 ).…”
Section: Current Strategies Of Therapeutic Peptides In Cadmentioning
confidence: 99%